1998
DOI: 10.1103/physrevlett.81.1239
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Electronic Topological Transition in Zinc under High Pressure?

Abstract: An electronic topological transition (ET T) in Zn was recently deduced from an anomaly in the Lamb-Mössbauer factor f at 6.6 GPa [Potzel et al., Phys. Rev. Lett. 74, 1139(1995]. We show by inelastic neutron scattering up to 9.4 GPa that the pressure dependence of the low energy acoustic phonon modes S 4 , S 3 , and T 4 is completely regular without any singularity over the entire pressure range. No phonon softening was found beyond 6 GPa, in contrast to the Mössbauer studies. Lattice dynamical calculations dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 26 publications
(59 reference statements)
3
39
0
Order By: Relevance
“…9 Inelastic neutron-scattering experiments on Zn showed no anomaly in the acoustic phonon frequency up to 9.4 GPa at room temperature. 10 Ramanscattering experiments showed no discontinuity in the optical phonon frequency up to 58 GPa at room temperature, although an indication of the ETT was suggested in the change in the Raman peak width. 11 These experimental results indicate that there is no anomaly in the lattice dynamics of Zn under pressure at room temperature.…”
mentioning
confidence: 87%
“…9 Inelastic neutron-scattering experiments on Zn showed no anomaly in the acoustic phonon frequency up to 9.4 GPa at room temperature. 10 Ramanscattering experiments showed no discontinuity in the optical phonon frequency up to 58 GPa at room temperature, although an indication of the ETT was suggested in the change in the Raman peak width. 11 These experimental results indicate that there is no anomaly in the lattice dynamics of Zn under pressure at room temperature.…”
mentioning
confidence: 87%
“…Morgan et al 14 argued that phonon softening may occur at pressures higher than 8.8 GPa through collapse of the Kohn anomaly via an ETT. Subsequent inelastic n-scattering studies to 9.4 GPa by Klotz et al 15 of acoustic phonon modes found regular behavior of the ⌺ 3 , ⌺ 4 , and T 4 modes, i.e., the anomaly found by Morgan et al 14 could not be verified, and their lattice-dynamical calculations demonstrated that the strong decrease in f cannot be due to kϭ0 phonon modes sensitive to the occurrence of an ETT.…”
Section: Introductionmentioning
confidence: 93%
“…In this context it should be noted that there were arguments 15 that the change of f might be an artifact due to a phase transition in the pressure transmitting medium used in the Mössbauer experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of possible single or multiple anomalies in c/a ratio at pressures ranging from 9 GPa to over 25 GPa have been both attributed 3 and not attributed 12 to ETT; one study 13 found evidence for multiple ETTs at pressures up to 130 GPa that did not affect the compressional behaviour of Os, and a further study 14 concluded that there are no peculiarities in the pressure-driven evolution of the atomic and electronic structure of Os. The inconsistencies in the theoretical highpressure behaviour of Os mirror the difficulties encountered when probing the high-pressure behaviour of 3d hcp metals such as Zn and e-Fe (refs [15][16][17][18][19]. These difficulties add further interest to detailed studies of the 5d element Os, to allow a broader comparison of the crystal chemistry of hcp metals.…”
mentioning
confidence: 94%